Excessive Treadmill Training Produces different Cardiac-related MicroRNA Profiles in the Left and Right Ventricles in Mice - Yang, Jing; Xu, Lin; Yin, Xin; Zheng, Yi Li; Zhang, Hai Peng; Xu, Sheng Jia; Wang, Wei; Wang, Sen; Zhang, Chen Yu; Ma, Ji Zheng (International Journal of Sports Medicine, 2021)
High-volume training followed by inadequate recovery may cause overtraining. This process may undermine the protective effect of regular exercise on the cardiovascular system and may increase the risk of pathological cardiac remodelling. We evaluated whether chronic overtraining changes cardiac-related microRNA profiles in the left and right ventricles. C57BL/6 mice were divided into the control, normal training, and overtrained by running without inclination, uphill running or downhill running groups. After an 8-week treadmill training protocol, the incremental load test and training volume results showed that the model had been successfully established. The qRT-PCR results showed increased cardiac miR-1, miR-133a, miR-133b, miR-206, miR-208b and miR-499 levels in the left ventricle of the downhill running group compared with the left ventricle of the control group. Similarly, compared with the control group, the downhill running induced increased expression of miR-21, miR-17–3p, and miR-29b in the left ventricle. Unlike the changes in the left ventricle, no difference in the expression of the tested miRNAs was observed in the right ventricle. Briefly, our results indicated that overtraining generally affects key miRNAs in the left ventricle (rather than the right ventricle) and that changes in individual miRNAs may cause either adaptive or maladaptive remodelling with overtraining.
Keywords: excessive training; aerobic training; myocardial; microRNAs